O uso da toxina botulínica tipo a no tratamento da espasticidade dos membros inferiores em crianças com paralisia cerebral: revisão sistemática - Blumetti, Francesco Camara [UNIFESP] (2016)
Introduction: Cerebral Palsy (CP) is the most common cause of physical disabilities in children in developed countries. The most common motor disturbance in CP is spasticity, and its control is one of the most challenging aspects of treating these patients. Botulinum toxin A (BTX-A) has been used in the past decades to induce a focal neuromuscular block in CP, potentially controlling the harmful effects of spasticity. Purpose: To evaluate the safety and effectiveness of BTX-A in the treatment of lower limb spasticity in CP, in regards to walking ability, function, joint range of motion and satisfaction. Method: This was a systematic review of randomized controlled trials (RCT), conducted according to the methods recommended by the Cochrane Collaboration. We searched the following electronic databases: MEDLINE, CENTRAL, EMBASE, CINAHL, SSCI and CPCI-S. There were no date or language restrictions. The last search was performed in December 2014. We included studies involving children with CP, where BTX-A injections in the lower limb muscles were compared to other interventions. The primary outcomes were gait analysis and function. The secondary outcomes were joint range of motion, satisfaction, quality of life and the measure of spasticity. Two independent authors performed study selection, methodological evaluation, and data extraction. A third author was consulted in case of disagreements. Study quality was evaluated with the Cochrane risk of bias tool. The quality of the evidence for every main outcome was graded according to the GRADE method. A quantitative analysis of available data was conducted whenever possible. Dichotomous data were analyzed using relative risks. Continuous data were analyzed using the mean difference. For all statistic tests, we considered a 5% significance level. We assessed heterogeneity by a visual analysis and the test > 50%. Results: We found 26 RCT, randomizing a total of 1137 participants. The use of BTX-A in the lower limb muscles was compared to: (1) usual care or physiotherapy, (2) placebo or ?sham?, (3) serial casting, (4) orthoses. For comparison 1 (11 studies), low and very low quality evidence showed that BTX-A was more effective to improve gait in the medium-term and function in the short-term. We also found some evidence of higher joint range of motion and satisfaction in the BTX-A group, although a higher rate of adverse events was noted. For comparison 2 (10 studies), moderate and high quality evidence showed that BTX-A was more effective to improve gait in the short- and medium-term, but not function in any term. No differences between groups were seen on joint range of motion and adverse events, although higher levels of satisfaction were seen in the BTX-A group. For comparison 3 (4 studies), low and moderate quality evidence showed no difference between groups in gait pattern in the short- and medium-term, and function in any term. Ankle range of motion and the rate of adverse events were similar between groups. For comparison 4 (1 study), very low quality evidence showed higher improvements in function and hip range of motion. Conclusion: When compared to placebo or a non-placebo control, BTX-A was effective to improve gait and satisfaction. The rate of adverse events with BTX-A was similar to placebo. BTX-A was also more effective than orthoses to improve function and range of motion. However, BTX-A was not shown to be more effective than ankle serial casting for any of the assessed outcomes.